Analisis Pengaruh 7P melalui Kepuasan Pelanggan terhadap Pemakaian Ulang InDrive Motor - Ihsan Lubis; Nuskha Ilma Arini (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to evaluate the influence of the 7P marketing mix on the decision to reuse InDrive Motor services, with customer satisfaction as a mediating variable using Structural Equation Modeling (SEM). The method used is quantitative with an explanatory design to analyze the influence between variables and the role of customer satisfaction as a mediator. The results show that Product (X1) has a positive and significant effect on customer satisfaction, while Price (X2) has a negative but insignificant effect. The variables Place (X3), People (X5), and Physical Evidence (X7) are positively related but not significant, while Promotion (X4) and Process (X6) were excluded due to multicollinearity. Customer satisfaction (M) plays a significant role in increasing reuse (Y), and only Product (X1) has a significant effect through this variable. Overall, these results confirm that although most of the 7P elements are insignificant, customer satisfaction remains a major factor in encouraging continued use of InDrive Motor services.